A Quest for Self- Realization in Zora Neale Hurston's Their Eyes Were Watching God: Exploring Self-Realization and Identity in Zora Neale Hurston's Their Eyes Were Watching God (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper aims to analyze self - realization and quest for identity in Hurston's Their Eyes Were Watching God. In her novel, she depicts characters who attempt to capture them-selves dependent on their internal wants and musings. Numerous notes and waves in the story show the idea of the fundamental role of self-hood and personality changes as she reveals to the new conditions, real factors, and encounters. Hurston's tale Their Eyes Were Watching God is an excellent work. Hurston delineates the life of an African American lady Janie who fantasies about happiness. Surviving through all complexities at long last, she triumphs and gets satisfaction. Janie doesn't think beyond practical bound-aries, yet she has a straightforward dream of bliss, which she finds in herself. The topic of self-acknowledgment or journey for identity is simply the principle topic in Hurston's fic-tion. Hurston was herself occupied with her mission for personality until she settled with writing as her career. This disarray which she confronted herself is apparent in her protagonist's lives. Her characters are looking for their personality like Hurston. At the beginning and the end, Janie is in search for self-identity and a journey for independent life. Janie is a dark lady who needs to liberate herself from social constraints, and she needs to become independent. This paper concludes that Janie in Their Eyes Were Watching God increases an incredible accomplishment looking for her self-acknowledgment and her feminine identity.